MULTILEVEL OSTEOSYNTHESIS OF THE LOWER EXTREMITIES BY THE ILIZAROV METHOD TO ELIMINATE DEFORMITIES AND SHORTENINGS IN CHILDREN AND ADOLESCENTS - Jumayeva, Jahongirovna Mahlie (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
-